2011
DOI: 10.3945/jn.111.143172
|View full text |Cite
|
Sign up to set email alerts
|

Fat Mass Is Inversely Associated with Serum Carboxymethyl-Lysine, An Advanced Glycation End Product, in Adults,

Abstract: High levels of circulating advanced glycation end products (AGE) are associated with cardiovascular disease, diabetes, chronic kidney disease, and increased mortality, but factors that influence levels of circulating AGE are not well known. Our objective was to characterize the relationship between serum carboxymethyl-lysine (CML), a major circulating AGE, and body composition in adults. In a cross-sectional study, total body DXA was performed and serum CML was measured in 592 adults, aged 26-93 y, from the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 39 publications
10
49
0
1
Order By: Relevance
“…We and others have shown that plasma AGEs are related to adiposity [14,[73][74][75]. In the present study, we confirm these findings by showing the negative association between circulating levels of CML and various measures of adiposity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We and others have shown that plasma AGEs are related to adiposity [14,[73][74][75]. In the present study, we confirm these findings by showing the negative association between circulating levels of CML and various measures of adiposity.…”
Section: Discussionsupporting
confidence: 81%
“…It has been proposed that the inverse cross-sectional relationship between circulating AGEs and adiposity may be a direct result of AGEs preferentially depositing in the adipose tissue as opposed to the circulation. This could be due to the fact that adipocytes are known to express CD36, a scavenger receptor that binds AGEs and facilitates endocytosis and degradation of AGEs [75].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found the same relationship and specifically confirmed the presence of CML in adipose tissue 17,18 . Taken together, it appears that CML is preferentially deposited in fat tissue and acts as an important mechanism involved in the dysregulation of adipokines in obesity, thereby contributing to the development of obesity-associated insulin resistance.…”
Section: Relationship Between Mid-gestational CML Glucose Indices Ansupporting
confidence: 61%
“…Thus, fat mass could influence circulating AGE concentrations through a role in the catabolism and breakdown of AGE. At the same time however, the CML/RAGE-axis appears to be a key modulator of obesity-induced dysregulation of adipokine expression in adipocytes and of subsequent insulin resistance 17 .…”
Section: Discussionmentioning
confidence: 99%
“…33 Nevertheless, these epidemiological studies do not encounter the underlying mechanism. Our present data provide a mechanistic explanation for these findings.…”
Section: /Leptrmentioning
confidence: 99%